ОСОБЛИВОСТІ НОРМАТИВНО-ПРАВОВОГО РЕГУЛЮВАННЯ ФІНАНСУВАННЯ ЖИТЛОВОГО ФОНДУ В УКРАЇНІ - Danchak, L.I.; Kozyk, V.V. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2011)
The paper analyses the current normative and legal base for regulating financing of the housing stock in Ukraine. The author has systemized it according to the mechanism of housing financing and the character of acquiring of the housing real estate. The contradictions, drawbacks and problematic aspects in regulation of the housing sector development have been revealed, as well as in the relations arising in the process of financing of Ukraine’s housing building. The directions of normative and legal regulation of housing financing from the funds which comprise the institutes of joint associated investing have been evaluated. Legal contradictions in the part of allocation of financial resources for the housing building have been identified.